2009
DOI: 10.1111/j.1540-8159.2008.02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation of Atrial Flutter Induces the Release of Platelet and Leukocyte‐Derived Procoagulant Microparticles and a Prothrombotic State

Abstract: RF ablation of common flutter induces a prothrombotic state and the release of platelet and leukocyte-derived procoagulant microparticles. Whereas this activation of blood coagulation could be viewed as clinically marginal in right-sided procedures, its relevance in left-sided procedures should be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A study of patients having RFCA for AFL demonstrated that ablation causes release of procoagulant microparticles derived from platelets and leukocytes but not from endothelium. 543 The thrombotic complications of RFCA reported in multiple adult studies were reviewed by Zhou et al 544 The thromboembolic complication rate ranged from 0% to 2%. Most of these studies reported systemic heparinization during the ablations, particularly when ablating on the left side.…”
Section: Radiofrequency Catheter Ablationmentioning
confidence: 99%
“…A study of patients having RFCA for AFL demonstrated that ablation causes release of procoagulant microparticles derived from platelets and leukocytes but not from endothelium. 543 The thrombotic complications of RFCA reported in multiple adult studies were reviewed by Zhou et al 544 The thromboembolic complication rate ranged from 0% to 2%. Most of these studies reported systemic heparinization during the ablations, particularly when ablating on the left side.…”
Section: Radiofrequency Catheter Ablationmentioning
confidence: 99%
“…Because the number of thromboembolic complications of RFA is low, identification of the risk factors is difficult and the significance of the pathophysiological mechanisms of hemostasis activation during RFA has not been definitively established in studies published to date. T0 before insertion of sheaths, T1 end of EPS, T2 30 min after completion of RFA, DD D-dimers, TAT thrombin-antithrombin III, PAI-1 plasminogen activator inhibitor type 1, t-PA tissue-type plasminogen activator, CPAi circulating platelet aggregates index, LCL lower confidence level, UCL upper confidence level Potential mechanisms of thrombogenesis during ablation procedures are multiple and include endothelial disruption, coagulation necrosis, electroporation injury, mechanical damage of the vessel wall, and heating of circulating blood elements by RF energy [9][10][11][12][13][14][15][16][17][18]. Sasano et al [19] concluded that the thrombogenesis caused by RFA has 2 phases; in the acute phase hemostasis activation occurs during placement of the catheters and in the delayed phase thrombogenesis is the result of endothelial damage caused by the RF current.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated RFCA to be associated with pre-thrombosis 4 33 . Thrombosis may occur inside the heart chamber or in artery and vein blood vessels in the peripheral regions after RFCA 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Although favorable outcomes have been reported following the use of RFCA, some potential serious complications are still evident. Significant risks include thromboembolic complications, vein vascular endothelial injuries, infection, bleeding, cardiac perforation with or without cardiac tamponade, valvular damage, and risks associated with the procedure or sometimes with the radiation itself 2 4 . It has been reported that RFCA may result in the formation of asymptomatic lower limb deep vein thrombosis (LDVT) 5 6 .…”
mentioning
confidence: 99%